Accidental ecosystem restoration? Assessing the estuary-wide impacts of a new ocean inlet created by Hurricane Sandy. (31st May 2019) - Gobler, Christopher J.; Young, Craig S.; Goleski, Jennifer; Stevens, Alexandra; Thickman, Jake; Wallace, Ryan B.; Curran, Patrick; Koch, Florian; Kang, Yoonja; Lusty, Mark W.; Hattenrath-Lehmann, Theresa K.; Langlois, Kylie; et al.
Abstract: Barrier island lagoons are the most common type of estuary in the world and can be prone to eutrophication as well as the formation and closure of ocean inlets via severe storm activity. This study describes the biological, chemical, and physical changes that occurred along the south shore of Long Island, NY, USA, following the formation of a new ocean inlet in eastern Great South Bay (GSB) by Hurricane Sandy in October of 2012. Time series sampling and experiments were performed at multiple locations within GSB and neighboring Moriches Bay from 2013 through to 2018. Historical comparisons to prior water quality monitoring data, fecal coliform concentrations, and hard clam growth rates were also made. Measurements indicated that the New Inlet provided asymmetrical ocean flushing. Within locations north (Bellport Bay) and east (Narrow Bay, western Moriches Bay) of the New Inlet, water residence times, summer water temperatures, total and dissolved nitrogen, chlorophyll a, the harmful brown tide alga, Aureococcus anophagefferens, pigments associated with diatoms and dinoflagellates (fucoxanthin and peridinin), and fecal coliform bacteria levels all significantly decreased, while salinity, dissolved oxygen, and water clarity significantly increased. In contrast, waters west of the New Inlet within the center of GSB experienced little change in residence times, significant increases in chlorophyll a and harmful brown tides caused by A. anophagefferens, as well as a significant decrease in water clarity and summer dissolved oxygen levels. Growth rates of juvenile hard clams ( Mercenaria mercenaria ) near the New Inlet increased compared to before the inlet and were significantly higher than in central GSB, where growth rates significantly declined compared to before the inlet. Hence, while enhanced ocean flushing provided a series of key ecosystem benefits for regions near the New Inlet, regions further away (> 10 km) experienced more frequent HABs and poorer performance of bivalves, demonstrating that enhanced ocean flushing provided by the breach was not adequate to fully restore the whole GSB ecosystem. Graphical abstract: Image 1 Highlights: In 2012, Hurricane Sandy breached Fire Island and formed the "New Inlet". The New Inlet has decreased residence time within Great South Bay. Increased flushing has significantly improved water quality near the New Inlet. Despite the creation of the New Inlet, central Great South Bay was mostly unaffected. The New Inlet may improve the growth and performance of bivalves.